A atuação internacional do Brasil para as mudanças climáticas: as COP De 2009 A 2015 - Rodrigues, Elze Camila Ferreira (2016)
During the fifteenth edition of the Conference of the Parties of the UNFCCC, the Brazilian diplomatic representation took a voluntary commitment to reduce national emissions of greenhouse gas effect. This was an outstanding event in the international climate change regime and in the trajectory of Brazilian environmental foreign policy because of the country's pioneering among the intermediaries economies that do not belong to Annex I. This attitude of Brazilian diplomacy is a part of the framework experienced by environmental multilateralism where the traditional division between North-South includes now the intermediate category of emerging economies. The performance of Brazil and other countries in that category was reflected in the discussions in the years after COP-15. The aim of this study is to analyze the performance of Brazilian diplomacy between the COP-15 and COP-21 concerning the challenges of climate change and multilateralism. Therefore, it is an analysis of the Brazilian environmental foreign policy during this period as well as a comparison with the performance of the BASIC countries in the same timeline